An overview of ceramic materials and their composites in porous media burner applications. Issue 8 (15th April 2021) - Chalia, Sonia; Bharti, Manish Kumar; Thakur, Preeti; Thakur, Atul; Sridhara, S.N.
Abstract: The alarming rate at which the available fossil fuel-based resources are depleting has raised grave concerns among all stakeholders about the future of the world. These limited energy resources play a very significant role in conventional energy generation techniques and processes. Traditional energy consumption devices must be made more efficient to prolong the availability of fossil fuels. Along with achieving a substantial increase in the efficiency of these devices, it is the need of the hour to focus on minimizing the hazardous emissions resulting from improper combustion and inefficient design, leading to the ever-growing issue of climate change. Porous burners are one of the few energy consumption devices that are known to facilitate efficient combustion along with low emissions of detrimental combustion products. In the porous burner technology, ceramic-based porous media deliver better performance due to their superior physical, chemical, and thermal characteristics compared to metal-based media. The present paper, therefore, provides an overview of the application of different ceramic-based porous media in burner technology. Advancements, particularly over the last twenty years, in the development and use of novel ceramic composites for porous burner applications, have also been discussed.